Outcomes of diuretics in rheumatic heart disease with compensated chronic heart failure: a retrospective study. (17th September 2020) - Liu, Cheng; Lai, Yanxian; Guan, Tianwang; Shen, Yan; Pan, Yichao; Wu, Deping
Abstract: Aims: The purpose of this retrospective propensity score‐matched study was to evaluate the superiority of different application approaches [continuous diuretics use (CDU) vs. intermittent diuretics use (IDU)] and types [loop diuretics (LDs) vs. thiazide diuretics (TDs)] of diuretics on long‐term outcomes for rheumatic heart disease (RHD) patients with compensated chronic heart failure (CHF). Methods and results: A total of 494 RHD patients with compensated CHF were analysed after propensity score matching. Cox proportional hazards regression model was used to investigate the associations of different diuretic application approaches and types with all‐cause mortality, cardiovascular death (CVD), and cerebrovascular death. Binary logistic regression analyses were used to evaluate the associations of different diuretic application approaches and types with 1‐, 3‐, and 5‐year heart failure (HF) re‐hospitalization as well as new‐onset atrial fibrillation (AF). In the comparison between IDU and CDU strategies for RHD patients with compensated CHF, CDU was associated with increased risks of all‐cause mortality [adjusted hazard ratio (HR) = 2.47, 95% confidence interval (CI): 1.54–3.97, P  < 0.001] and CVD (adjusted HR = 3.67, 95% CI: 1.95–6.89, P  < 0.001) except cerebrovascular death (adjusted HR = 1.07, 95% CI: 0.34–3.41, P  = 0.905). CDU was also associated with increased risks of 3‐year [adjusted odds ratio (OR) = 1.80, 95% CI: 1.09–2.96, P  = 0.022] and 5‐year (adjusted OR = 2.02, 95% CI: 1.18–3.45, P  = 0.010) HF re‐hospitalization risk and new‐onset AF (adjusted OR = 2.34, 95% CI: 1.31–4.20, P  = 0.004) except 1‐year HF re‐hospitalization risk (adjusted OR = 1.54, 95% CI: 0.88–2.70, P  = 0.130). In the comparison between TDs and LDs among study participants receiving IDU strategy, LDs were only associated with decreased 1‐year HF re‐hospitalization risk (adjusted OR = 0.30, 95% CI: 0.12–0.77, P  = 0.012) rather than all‐cause mortality, CVD, cerebrovascular death, 3‐ and 5‐year HF re‐hospitalization, and new‐onset AF (all adjusted P  > 0.05). In the comparison between TDs and LDs among study participants receiving CDU strategy, LDs were not associated with cerebrovascular death and 1‐year HF re‐hospitalization (both adjusted P  > 0.05) but with increased risks of all‐cause mortality (adjusted HR = 1.80, 95% CI: 1.09–2.99, P  = 0.023), CVD (adjusted HR = 1.89, 95% CI: 1.04–3.44, P  = 0.037), 3‐year (adjusted OR = 1.91, 95% CI: 1.06–3.43, P  = 0.031) and 5‐year (adjusted OR = 2.16, 95% CI: 1.12–4.19, P  = 0.022) HF re‐hospitalization, and new‐onset AF (adjusted OR = 2.66, 95% CI: 1.25–5.68, P  = 0.012). Conclusions: Continuous diuretics use (especially LDs) was associated with increased risks of all‐cause mortality, CVD, medium‐term/long‐term HF re‐hospitalization, and new‐onset AF in RHD patients with compensated CHF.